THE CAUSATIVE AS A MULTIFACETED FORM OF THE VERB VOICE: THE CASE OF THE BASHKIR LANGUAGE - Salyakhova, Z.I.; Samsitova, L.H.; Khusainova, L.M.; Abdullina, L.B.; Sultakaeva, R.A. (International Journal of Psychosocial Rehabilitation, 2020)
The category of voice is one of the most important and controversial topics not only in the theory of the Bashkir language but also in Turkology and linguistic studies as a whole. A considerable amount of works by Turkic scholars have been dedicated to this linguistic phenomenon, but the issue of the verb voice, including the causative ("coercive") voice, is still open to discussion.This article deals with different points of view on the causative in Turkology. It also provides an analysis of structural and semantic aspects of the causative.The results of academic research and the theoretical constructs considered in this article are significant for comparative and historical studies of the Turkic languages.Within the frames of our study, we performed a functional-semantic analysis of the phenomenon with the use of comparative-historical, structural-semantic and descriptive methods. In our study we have used fragments from the works of classical and modern Bashkir literature, oral folklore and printed materials from periodicals. The results of our study confirm that the causative is a complicated multifaceted form of the verb voice, which is frequently used in the Bashkir language in a wide variety of forms and meanings. In the Bashkir language the causative is expressed through causative affixes and exhibits a variety of semantic nuances. The causative forms of Bashkir verbs are characterised by iteration of multiple voice affixes. The causative is part of the system of the verb voice in the Bashkir language. It is very important for further development of the Bashkir and general Turkic linguistic studies to continue research in this area